PERBEDAAN KUALITAS TIDUR PASIEN PENYAKIT JANTUNG KORONER BERDASARKAN PITTSBURGH SLEEP QUALITY INDEX (PSQI) DAN SLEEP QUALITY SCALE (SQS) (STIKES Telogorejo Semarang, 2023)
Sleep disturbance is one of the disorders experienced by coronary heart patients. There is no standard instrument to assess sleep quality in hospitalized patients with coronary heart disease. Objective: To analyze differences in sleep quality in patients with coronary heart disease using two different scales, namely the Pittsburgh Sleep Quality Index (PSQI) and Sleep Quality Scale (SQS). Methods: This type of research is a comparative descriptive study with a cross sectional approach using PSQI and SQS questionnaires. The population that will be used as a study is patients with coronary heart disease in the SMC Cardiology Polyclinic, Telogorejo Hospital. The sample used by researchers using non-random sampling. With a total population of 126 respondents, 63 respondents used the PSQI questionnaire and 63 respondents used the SQS. Results: Based on the sleep quality of patients using the PSQI questionnaire, 42 respondents (66.7%) had poor sleep quality, while using the SQS questionnaire 38 respondents (60.3%) had good sleep quality. From the results of the Mann Whitney test, p-value: 0.003 <0.05, it means that there is a significant difference between the PSQI and SQS questionnaires. For further researchers, it is hoped that they can assess the quality of sleep of patients using other questionnaires.